A Theoretical Compatible Investigation to Estimate the Electrical Conductivity in Weakly Ionized Plasma Gases - Abdulmohsin Ali, Mohammed; Hameed Majeed, Raad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The main goal of this work is to achieve an acceptable agreement between the obtained results and previously published results of the electrical conductivities of Krypton and Xenon weakly ionized plasma gases, which are strongly affected by the electron number density Ne and electron collision frequency. When the electron energy distribution function (EEDF) is calculated, it shows a decrease with increasing the energy for all reduced electric field values (E/N). The above calculations are done in terms of the Boltzmann transport equation solution by using a numerical technique based on the two-term approximation method, which is represented by the common code "BOLSIG+." Calculated electrical conductivities of each Xenon and Krypton gas showed a rapid increase in electrical conductivity with electron temperature Te in the low-temperature range, and then the increase was slower until it reached a constant value (the saturation region). The present work results show an acceptable agreement with the previously published results